Triadic Reciprocal Determinism and Rational Choice Theory: A Case Study of Rohingya Refugee - Dasadwiastaning, Valentia Nadya (International Journal Labs, 2022)
Background: The similarities among the refugee looks like a phenomenon that needs further research. Those theories are a part of behaviorism and the decision-making approach. It can be used to predict alternatives choice and also which alternatives the actor or agent will determine. Aim: This study tries to analyze the behavior of Rohingya refugees with triadic reciprocal determinism and rational choice theory. It also profoundly concerns how the decision to act adopted by refugees is almost similar, whether in steps or goals. Method: This research uses a qualitative approach and sources from journals, articles, and interviews from online news. All the data sources will be analyzed with the theory already mentioned above. Findings: While Rohingya get safe and are placed in a temporary camp, some flee and do not want to wait for status determination. They have similar goals and behaviors that guide them to choose better alternatives. Being smuggled by a third party is one of the rational choices they make. That choice is determined based on behavior that constructs their rationale. Factors in triadic reciprocal determinism are also related to alternatives choice that they make, which is part of the social cognitive process.